The Fractional CO2 Laser for the Treatment of Genitourinary Syndrome of Menopause: A Prospective Multicenter Cohort Study. Issue 5 (19th November 2020) - Li, Jingran; Li, Huan; Zhou, Yanfei; Xie, Meiqing; Miao, Yali; Wang, Luwen; Zhao, Yan; Ying, Ting; Hu, Yan; Chen, Yu; Chen, Yaxiao; Sun, Xiuli; et al.
Abstract : Background and Objectives: Genitourinary syndrome of menopause (GSM) is a common condition affecting of most postmenopausal women, which greatly impacks the quality of life, and need to treat. This prospective multicenter cohort study aimed to compare the efficacy and safety of the fractional carbon dioxide (CO2 ) laser with that of topical estrogen for vaginal treatment and relieving symptoms of genitourinary syndrome of menopause (GSM). Study Design/Materials and Methods: This study included 162 postmenopausal patients who received vaginal laser or topical Estriol cream therapy between January 2017 and May 2019 at eight study centers in China. The degree of GSM‐related symptoms (vaginal burning, dryness, and dyspareunia) was evaluated using the Vaginal Health Index score (VHIS) and Visual Analog Scale (VAS) at baseline, 1, 3, 6, and 12 months posttreatment. The primary endpoint was the improvement in vaginal burning, dryness, and dyspareunia at 6 months after treatment. Multivariate logistic regression was used to compare the rate of improvement in the two groups. Results: At baseline, the laser and control groups showed no significant difference in the mean age, time after menopause, and the VHIS (all P > 0.05). In the laser group, compared with baseline, significant differences were seen in the VHIS after the first or second treatment session and at 1, 3, 6, and 12 months posttreatment ( P < 0.01). In the control group, compared with baseline, the VHIS showed significant differences after 1, 3, and 6 months of treatment ( P < 0.05). However, there was no significant difference after 3 and 6 months of follow‐up between the two groups ( P > 0.05). The VHIS scores were significantly higher after 1 month (16.63 ± 2.79 vs. 15.57 ± 2.43) and 12 months (15.72 ± 2.59 vs. 12.12 ± 4.08) of treatment in both the groups ( P < 0.05). At 6 months after treatment, both groups showed improvement in vaginal burning, vaginal dryness, and dyspareunia ( P > 0.05). The VAS findings at 6 months posttreatment were significantly different when compared with the pretreatment findings ( P < 0.001). There were no significant adverse effects in the two groups. Conclusions: Fractional CO2 laser vaginal treatment could be a safe and effective option for treating symptoms of GSM, including vaginal burning, dryness, and dyspareunia. The improvement in symptoms was comparable with that seen with topical estrogen therapy and lasted for at least 6–12 months posttreatment. Lasers Surg. Med. © 2020 Wiley Periodicals LLC